A practical approach for teaching digital image processing with MATLAB - E.Jebamalar Leavline,; D.Asir Antony Gnana Singh, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Nowadays in the new era of Information technology, the use of visual aids in teaching and learning process is inevitable. Image processing is an interesting field that studies about various processing techniques for digital images, which is the basis of the emerging visual communication. Teaching the image processing has been a challenge since it requires imagination and creativity to some extent for the students to understand the concepts of image processing. MATLAB is a computing platform that is suitable for developing and testing a number of applications. The major advantage of using MATLAB is the graphical user interface (GUI) which can contribute positively to understand the concepts with ease. The pictorial illustrations confer better understanding of the concepts with ease. This article addresses a novel method of teaching the concepts of image processing with MATLAB. It also provides an insight to some of the basic image processing techniques namely image restoration, image denoising, image segmentation and edge detection with examples using MATLAB.